Theoretical and experimental investigation in prediction of tool life in preheated machining of AISI 02 hardened steel - Lajis, M. A.; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Turnad L., Ginta (IIT Madras, 2008)
The tool life of TiAlN coated carbide tools was investigated at various combinations of cutting speed, feed and preheating temperature in end milling of AISI 02 hardened steel under room temperature and preheated machining conditions. Sufficient number of experiments was conducted based on the central composite design (CCD) which was adopted by response surface methodology (RSM) to generate tool life prediction values. The experimental results show that preheated machining led to appreciable increasing tool life compared to room temperature machining. The percentage of tool life increase was between 190-315 % depending on preheating temperature. Preheating of the work material with higher heating temperatures (250-450 0c) gives significant improvement in terms of tool life